Analysis of the effect of Dividend policy, Debt Policy on Firm Value with Profitabilits as an Innterveneing Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange for the period 2018-2022 - Kodi, Hutriana; Wiyono, Gendro; Rinofah, Risal (Ekonomis: Journal of Economics and Business, 2024)
The study is entitled “The Effect of Dividend Policy, Debt Policy on Firm Value with Profitability as an Intervening Variable in Manufacturing Companies listed on the Indonesian Stock Exchange 2018-2022 Period”. With the aim of knowing the results of the analysis of the effect of dividend policy (DPR) on firm value (PBV), to find out the results of the analysis of the effect of debt policy (DER) on firm value (PBV), to find out the results of the analysis of the effect of profitability (ROA) on firm value (PBV). ), to find out the results of the analysis of the effect of dividend policy (DPR) on profitability (ROA), to find out the results of the analysis of the effect of debt policy (DER) on profitability (ROA) in Manufacturing Companies listed on the Indonesia Stock Exchange in 2018-2022. And to prove the results of the analysis of the influence of dividend policy (DPR), debt policy (DER) on company value (PBV) with profitability (ROA) as an intervening variable. Sample selection used a purposive sampling technique using certain criteria so that 46 samples were obtained that met the criteria. Data analysis uses multiple linear regression and path analysis. The research results show that dividend policy influences company value, debt policy influences company value, profitability influences company value, dividend policy influences profitability, debt policy influences profitability and profitability is able to mediate the relationship between dividend policy and debt policy on company value.